The autopodial skeleton of Paracamelus aguirrei (Morales 1984) (Tylopoda, Mammalia) from the late Miocene site of Venta del Moro(Valencia, Spain) - Caballero, Oscar (2021)
Venta del Moro is a classical locality from the late Miocene (Ventian, MN13) of the Cabriel basin from Valencia (Spain). This site is the type locality of nine mammal species. Among them, is the camelid Paracamelus aguirrei, which was defined by its upper dentition, a lower third premolar (p3), and some postcranial remains. This genus, which is the only Neogene camelid present in Europe, rapidly expanded throughout Eurasia from North America. In this work, the autopodial elements of P. aguirrei recovered from Venta del Moro are described, among them some that were previously unknown. This study shows that P. aguirrei was considerably large, comparable in size to the giant camels of North America like Megacamelus merriami and the giant camels of Eurasia like Paracamelus gigas and Camelus knoblochi.